Period poverty and mental health of menstruators during COVID-19 pandemic: Lessons and implications for the future - Rohatgi, Aishwarya; Dash, Sambit (Frontiers in Global Women's Health, 2023)
Menstruation is a naturally occurring phenomenon; however, millions of adolescent girls and women, as well as non-binary persons who bleed every month, are deprived of menstruating safely and respectfully. Those belonging to marginalized sections face the brunt of lack of access to WASH facilities, affordable menstrual supplies, and inequitable distribution of menstrual health education and are victims of period poverty. Their pre-existing suffering was further exacerbated by the COVID-19 pandemic, which negatively affected the mental health of those menstruating. Adolescent girls and women in communities found it persistently challenging to access and afford menstrual products while deprived of menstrual hygiene education. These put them under immense stress and elevated financial liability, predisposing them to period poverty. Interventions addressing period poverty rely on mustering collective community voices and deploying adequate policy tools. All the efforts and solutions must provide social and financial protection nets and psychological aid through mental health support groups. It is core to drive menstrual health equity for all menstruators, irrespective of who they are, what they do, and where they live.